Rationale and design of PURE, a randomized controlled trial to evaluate Peritoneal Ultrafiltration with PolyCore™ in Refractory Congestive Heart Failure - Edoardo Gronda; Maurizio Gallieni; Giuseppe Pacileo; Giovambattista Capasso; Lee-Jen Wei; Francesco Trepiccione; Marco Heidempergher; Mario Bonomini; Marco Zimarino; José Carolino Divino-Filho; Lorenzo Di Liberato; Maria Michela Caracciolo; et al. (Karger Publishers, 2024)
Introduction: Peritoneal Ultrafiltration (PUF) has been proposed as an additional therapeutic option for Refractory Congestive Heart Failure (RCHF) patients. Despite promising observational studies and/or case report results, limited clinical trials data exist, and so far, PUF solutions remain only indicated for chronic kidney diseases (CKD). In this article, we describe a multicenter, randomized, controlled, unblinded, adaptive design clinical trial, about to start, investigating the effects of PolyCore™, an innovative PUF solution, in the treatment of RCHF patients. Methods: The Peritoneal Ultrafiltration in Cardiorenal Syndrome (PURE) study is a Phase II, multicenter, randomized, controlled, unblinded, adaptive design clinical trial that aims to evaluate the safety and efficacy of PUF, using PolyCore™ as the investigational solution, in the treatment of RCHF patients who present with prominent right ventricular failure due to afterload mismatch, functional tricuspid regurgitation and enlarged cava vein consequent to intravascular fluid overload. Approximately 84 patients will be randomized 1:1 either to continue with their prescribed guidelines-directed medical therapy or to add the PUF treatment on top of it. The primary objective is to evaluate if PUF treatment has an impact on the composite endpoint of the patient's mortality or worsening of the patient's condition such as hospitalization for cardiovascular causes, increasing the initial daily dose of loop diuretic or worsening of renal function. Statistical analysis for the primary endpoint will be standard survival analysis to estimate the failure rate at month 7 for each group via Kaplan-Meier curves. Sensitivity analysis and various secondary analyses, including a multiple events analysis, will be conducted to evaluate the robustness of the primary endpoint results. Safety will be evaluated for up to 12 months. Conclusion: The PURE Study was designed to evaluate the safety and efficacy of peritoneal ultrafiltration with PolyCore™ on top of guidelines-directed medical therapy in patients with RCHF, assuming a combined clinical endpoint of mortality or worsening patients' condition. If successful, the treatment should allow for an improvement of the RCHF symptoms, decreasing hospitalization rate of patients. ClinicalTrials.gov Identifier: NCT03994874